Systemic-Immune-Inflammation Index as a Promising Biomarker for Predicting Perioperative Ischemic Stroke in Older Patients Who Underwent Non-cardiac Surgery - Zhang, Faqiang; Niu, Mu; Wang, Long; Liu, Yanhong; Shi, Likai; Cao, Jiangbei; Mi, Weidong; Ma, Yulong; Liu, Jing (Frontiers in Aging Neuroscience, 2022)
Objective This study aimed to investigate the clinical prognostic values of the preoperative systemic-immune-inflammation index (SII) in older patients undergoing non-cardiac surgery, using perioperative ischemic stroke as the primary outcome. Methods This retrospective cohort study included older patients who underwent non-cardiac surgery between January 2008 and August 2019. The patients were divided into SII < 583 and SII ≥ 583 group according to the optimal SII cut-off value. The outcome of interest was ischemic stroke within 30 days after surgery. Primary, sensitivity, and subgroup analyses were performed to confirm that preoperative SII qualifies as a promising, independent prognostic indicator. Propensity score matching (PSM) analysis was further applied to address the potential residual confounding effect of covariates to examine the robustness of our results. Results Among the 40,670 included patients with a median age of 70 years (interquartile range: 67, 74), 237 (0.58%) experienced an ischemic stroke within 30 days after surgery. SII ≥ 583 was associated with an increased risk of perioperative ischemic stroke in multivariate regression analysis [odds ratio (OR), 1.843; 95% confidence interval (CI), 1.369–2.480; P < 0.001]. After PSM adjustment, all covariates were well balanced between the two groups. The correlation between the SII and perioperative ischemic stroke remained significantly robust (OR: 2.195; 95% CI: 1.574–3.106; P < 0.001) in the PSM analysis. Conclusion Preoperative SII, which includes neutrophil, platelet, and lymphocyte counts obtained from routine blood analysis, was a potential prognostic biomarker for predicting perioperative ischemic stroke after non-cardiac surgery in older patients. An elevated SII, based on an optimal cut-off value of 583, was an independent risk factor for perioperative ischemic stroke.